Preparation method of nearly spherical porous nano molybdenum powder
Molybdenum trioxide powder is prepared by rapid temperature-raising decomposition of molybdenum salt and hydrothermal method, and microcrystalline carbon spheres are prepared as nucleation agents with high-temperature carbonization. The MoO2-Mo hydrogen reduction process is controlled by hydrogen reduction and gradient temperature-raising, which solves the problem of difficult control of the particle size and distribution of molybdenum powder, and achieves the improvement of the quality and stability of ceramic metallization.
Patent Information
- Application Number
- CN202311855882.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-07-01
AI Technical Summary
The prior art is difficult to control the particle size and distribution of molybdenum powder, and there are problems of material agglomeration and uneven size distribution, which affects the quality and stability of ceramic metallization.
The molybdenum trioxide powder was obtained by rapid temperature-raising decomposing molybdenum salts, and the microcrystalline carbon spheres were prepared as nucleation agents by combining hydrothermal method and high-temperature carbonization. The MoO2-Mo hydrogen reduction process was controlled through hydrogen reduction and gradient temperature-raising to prevent particles from agglomerating and growing.
Molybdenum powder with finer particle size and nearly spherical pore structure was prepared, which solved the problem of difficult control of the particle size and distribution of molybdenum powder, and improved the quality and stability of ceramic metallization.
Smart Images

Figure CN120228279A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of nano-powder materials, and particularly relates to a method for preparing near-spherical porous nano-molybdenum powder. Background Art
[0002] With the development of vacuum electronic devices towards ultra-high frequency, high power and long life, the glass-to-metal sealing can no longer meet the requirements of tube manufacturing, and the ceramic-metal sealing process has gradually been put on the agenda. The common methods for ceramic-metal sealing are sintered metal powder method and active metal method. Others also include oxide solder method, vapor deposition process, solid-phase process, pressure sealing, electron beam welding, etc. The main difference between ceramic materials and metals is that it belongs to a brittle dielectric material. Generally, most solders cannot wet its surface or interact with it to form a firm bond. Even if a certain method is used to seal it with metal, if the thermal expansion coefficients of the two are quite different, it will cause cracking or air leakage. Therefore, ceramics and metals cannot be directly brazed with general solders. It is necessary to first coat a metal film that is firmly bonded to the porcelain and not easily melted on the ceramic surface, that is, to carry out so-called "ceramic metallization". The improvement of the quality and process stability of ceramic metallization can ensure that the device has high mechanical strength, high vacuum tightness and certain special properties. The main component in the metallization formula is generally refractory metal powder, such as molybdenum, tungsten, tantalum, rhenium, etc., and its melting point is generally more than 1000 °C higher than the metallization temperature. The most used is molybdenum powder, followed by tungsten powder.
[0003] At present, the particle size of molybdenum powder required in the ceramic metallization formula is 1.5 μm to 2.0 μm. However, in the actual use of molybdenum powder for metallization, it is very difficult to meet the above requirements for particle size and its distribution. There are problems of material agglomeration and uneven size distribution. The agglomerate morphology comes from the morphology transfer of raw material ammonium molybdate and molybdenum oxide. On the other hand, the chemical vapor transport process in the traditional hydrogen reduction process further inhibits the uniformity of the product size. Existing research shows that on the premise of not over-sintering, choosing fine molybdenum powder will be beneficial to the reverse migration of the glass phase in the capillary of alumina ceramic into the capillary of the metallization layer to obtain a firm metallization layer. The molybdenum powder is spherical or near-spherical, which is easy to make the microstructure of the metallization layer uniform, avoid local stress concentration caused by sharp corners, and avoid bridging between particles. In addition, the pore structure is beneficial to the penetration and migration of the glass phase during sintering. The physical and process properties of the raw material molybdenum powder in the metallization formula seriously affect the quality and stability of ceramic metallization. Therefore, it is crucial to prepare molybdenum powder with finer particle size and near-spherical pore structure. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing near-spherical porous nano-molybdenum powder in view of the deficiencies of the above-mentioned prior art. This method uses rapid heating to decompose molybdate to obtain molybdenum trioxide powder with good decomposability, avoiding the agglomeration problem of molybdate. At the same time, the hydrothermal method and high-temperature carbonization are used to obtain microcrystalline carbon spheres with good dispersibility and uniform size as nucleating agents for hydrogen reduction, avoiding the chemical vapor transport process during hydrogen reduction and hindering the agglomeration and growth of subsequent MoO2 and Mo powders. Then, gradient heating reduction is combined to control the chemical vapor transport and growth processes during the MoO2-Mo hydrogen reduction, thereby ensuring the dispersibility of Mo particles and the size of the pore structure, and solving the problem of difficult control of the particle size and distribution of molybdenum powder.
[0005] To solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing near-spherical porous nano-molybdenum powder, characterized in that the method comprises the following steps:
[0006] Step 1: Decompose molybdate at room temperature to obtain molybdenum trioxide;
[0007] Step 2: Carry out hydrothermal reaction carbonization with an organic carbon source, and wash and dry the reaction product to obtain carbon microspheres;
[0008] Step 3: Place the carbon microspheres obtained in Step 2 in a tubular furnace for high-temperature carbonization to obtain partially graphitized microcrystalline carbon spheres;
[0009] Step 4: Highly disperse and mix the molybdenum trioxide obtained in Step 1 with the microcrystalline carbon spheres obtained in Step 3 to obtain a uniform mixed material;
[0010] Step 5: Place the mixed material obtained in Step 4 in a tubular furnace for heat treatment to obtain near-spherical molybdenum dioxide powder;
[0011] Step 6: Carry out hydrogen reduction on the near-spherical molybdenum dioxide powder obtained in Step 5 in a hydrogen-containing atmosphere to obtain near-spherical porous nano-molybdenum powder.
[0012] In the above method for preparing near-spherical porous nano-molybdenum powder, the molybdate in Step 1 is ammonium molybdate, the temperature of the decomposition reaction is 500°C to 700°C, the time is more than 1 h, and the heating rate is greater than 30°C / min.
[0013] In the above method for preparing near-spherical porous nano-molybdenum powder, the organic carbon source in Step 2 is the water-soluble organic carbon source glucose, and the organic carbon source is prepared into a solution with a concentration of 0.3 mol / L to 1.2 mol / L; the temperature of the hydrothermal reaction is 150°C to 200°C, and the time is 12 h to 24 h. This organic carbon source is easy to obtain and has low cost, which is beneficial to obtaining carbon microspheres with controllable size and good uniformity.
[0014] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the drying treatment method in step two is freeze-drying method, the temperature does not exceed -40°C, the vacuum degree does not exceed 40 Pa, and the drying time is more than 8 h.
[0015] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the protective atmosphere used for high-temperature carbonization in step three is argon, the temperature is 500°C to 1000°C, the heat preservation time is 1 h to 3 h, and the heating rate is 5°C / min to 10°C / min.
[0016] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the molar ratio of molybdenum trioxide to microcrystalline carbon spheres in step four is 1:0.4 to 0.5. By controlling the molar ratio of molybdenum trioxide to microcrystalline carbon spheres, it is ensured that the amount of microcrystalline carbon spheres is sufficient to make the heat treatment reaction proceed smoothly, and excessive carbon is avoided, resulting in too high residual carbon content after the reaction and reducing the purity of the product.
[0017] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the mixed material is placed in an alumina crucible in step five, and the thickness of the material layer does not exceed 8 mm; the protective atmosphere used for the heat treatment is argon or nitrogen, the heat treatment temperature is 600°C to 750°C, the heat preservation time is 0.5 h to 2 h, and the heating rate does not exceed 30°C / min. In the present invention, by controlling the thickness of the material layer not to exceed 8 mm, it is avoided that the thickness of the material layer is too thin resulting in a low yield of molybdenum dioxide powder, and at the same time, it is avoided that the thickness of the material layer is too thick, resulting in too high concentrations of CO and CO2 gases during the carbon reduction process of the heat treatment, leading to uneven nucleation and growth of molybdenum dioxide and uneven size of its particles; by controlling the heat treatment temperature, it is avoided that too high temperature causes the volatilization of molybdenum trioxide and the loss of molybdenum source.
[0018] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the hydrogen-containing atmosphere used for hydrogen reduction in step six is an inert gas with a hydrogen volume fraction greater than 10%, the reduction adopts a gradient temperature rise reaction, the reaction temperature is 600°C to 900°C, and the heat preservation time for each stage is 0.5 h to 2 h, and the heating rate is 5°C / min to 20°C / min. In the present invention, by using an inert gas containing hydrogen as the hydrogen reduction atmosphere and combining with a gradient temperature rise reaction, the concentration of water vapor during the hydrogen reduction process is reduced, and the transfer of the spherical particle morphology is ensured.
[0019] The above-mentioned preparation method of nearly spherical porous nano-molybdenum powder is characterized in that the particle size of the nearly spherical porous nano-molybdenum powder in step six is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%. The nearly spherical porous nano-molybdenum powder prepared by the present invention has excellent properties and can be widely used in national defense and military industries such as military, aerospace and nuclear industries.
[0020] The present invention has the following advantages compared with the prior art:
[0021] 1. The present invention uses rapid heating to decompose molybdate to obtain molybdenum trioxide, avoiding the agglomeration problem during the decomposition of molybdate such as ammonium molybdate, and preparing molybdenum trioxide powder with good dispersibility.
[0022] 2. The present invention first uses hydrothermal reaction to carbonize to prepare carbon microspheres, and then combines high-temperature carbonization to further improve the degree of carbonization and graphitization, preparing partially graphitized microcrystalline carbon spheres, making the microcrystalline carbon spheres have the characteristics of good dispersibility and uniform size, and using the microcrystalline carbon spheres as nucleating agents during the reduction of molybdenum trioxide, effectively hindering particle agglomeration, avoiding the chemical vapor transport process during hydrogen reduction, and further hindering the agglomeration and growth of subsequent MoO2 and Mo powders, which is beneficial to obtaining molybdenum powder products with nano-scale particle size and uniform size distribution.
[0023] 3. The present invention controls the chemical vapor transport and growth process during the hydrogen reduction of MoO2 - Mo by adopting gradient heating reduction, ensuring the dispersibility of Mo particles and the size of the pore structure, and then controlling the product morphology, so as to obtain nearly spherical porous nano-molybdenum powder.
[0024] The technical solution of the present invention will be further described in detail below with reference to the drawings and embodiments. Description of the Drawings
[0025] Figure 1 It is the X-ray diffraction pattern of molybdenum trioxide prepared in Example 3 of the present invention.
[0026] Figure 2 It is the scanning electron microscope image of molybdenum trioxide prepared in Example 3 of the present invention.
[0027] Figure 3 It is the X-ray diffraction pattern of the microcrystalline carbon spheres prepared in Example 3 of the present invention.
[0028] Figure 4a It is the low-magnification scanning electron microscope image of the microcrystalline carbon spheres prepared in Example 3 of the present invention.
[0029] Figure 4b It is the high-magnification scanning electron microscope image of the microcrystalline carbon spheres prepared in Example 3 of the present invention.
[0030] Figure 5 It is the X-ray diffraction pattern of the nearly spherical molybdenum dioxide powder prepared in Example 3 of the present invention.
[0031] Figure 6a It is the low-magnification scanning electron microscope image of the nearly spherical molybdenum dioxide powder prepared in Example 3 of the present invention.
[0032] Figure 6bThis is a high-magnification scanning electron microscope image of the near-spherical molybdenum dioxide powder prepared in Example 3 of the present invention.
[0033] Figure 7 This is the X-ray diffraction pattern of the near-spherical porous nano-molybdenum powder prepared in Example 3 of the present invention.
[0034] Figure 8a This is a low-magnification scanning electron microscope image of the near-spherical porous nano-molybdenum powder prepared in Example 3 of the present invention.
[0035] Figure 8b This is a high-magnification scanning electron microscope image of the near-spherical porous nano-molybdenum powder prepared in Example 3 of the present invention. Detailed implementation manners
[0036] Example 1
[0037] This example includes the following steps:
[0038] Step 1: Place 120 g of ammonium molybdate in an alumina crucible with a length × width × height of 150 mm × 150 mm × 35 mm at room temperature, put it into a muffle furnace for decomposition reaction, the temperature of the decomposition reaction is 500 °C, the time is 1 h, and the heating rate is 35 °C / min. After the decomposition reaction is completed, cool it to room temperature to obtain molybdenum trioxide;
[0039] Step 2: Add 3.24 g of glucose to 60 mL of deionized water and stir until completely dissolved to form a transparent solution with a concentration of 0.3 mol / L. The stirring speed is 400 r / min, and the stirring time is 0.5 h. Then transfer the transparent solution to a 100 mL polytetrafluoroethylene reaction kettle for hydrothermal reaction carbonization. The temperature of the hydrothermal reaction is 150 °C, the time is 12 h. After the reaction is completed, naturally cool it to room temperature, take out the reaction product, wash it successively with absolute ethanol and deionized water and centrifuge for separation. After repeating the washing 4 times, perform freeze-drying at a temperature of -40 °C, a vacuum degree of 40 Pa, and a drying time of 8 h to obtain black carbon microspheres;
[0040] Step 3: Place 2 g of the carbon microspheres obtained in Step 2 in an alumina crucible with a length × width × height of 100 mm × 40 mm × 20 mm, put it into a low-temperature tube furnace for high-temperature carbonization. The protective atmosphere used is argon, the temperature is 500 °C, the holding time is 1 h, and the heating rate is 5 °C / min to obtain partially graphitized microcrystalline carbon spheres;
[0041] Step 4: Grind and highly disperse and mix the molybdenum trioxide obtained in Step 1 and the microcrystalline carbon spheres obtained in Step 3 according to a molar ratio of 1:0.4 to obtain a uniform mixed material;
[0042] Step 5: Place 5 g of the mixed material obtained in Step 4 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, with a layer thickness of 2 mm. Put it into a low-temperature tube furnace for heat treatment. The protective atmosphere used is argon, the heat treatment temperature is 650 °C, the holding time is 0.5 h, and the heating rate is 5 °C / min to obtain nearly spherical molybdenum dioxide powder;
[0043] Step 6: Place 10 g of the nearly spherical molybdenum dioxide powder obtained in Step 5 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and carry out hydrogen reduction in a hydrogen-containing atmosphere. The hydrogen-containing atmosphere used is an inert gas with a hydrogen volume fraction of 90%. The reduction uses a gradient heating reaction, and the reaction temperatures are 600 °C, 700 °C, and 750 °C in sequence. The holding time for each stage is 1 h, and the heating rate is 5 °C / min to obtain nearly spherical porous nano-molybdenum powder.
[0044] After testing, the particle size of the nearly spherical porous nano-molybdenum powder prepared in this example is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%.
[0045] Example 2
[0046] This example includes the following steps:
[0047] Step 1: At room temperature, place 180 g of ammonium molybdate in an alumina crucible with dimensions of length × width × height = 150 mm × 150 mm × 35 mm, and put it into a muffle furnace for decomposition reaction. The decomposition reaction temperature is 700 °C, the time is 3 h, and the heating rate is 50 °C / min. After the decomposition reaction ends, cool it to room temperature to obtain molybdenum trioxide;
[0048] Step 2: Add 13.0 g of glucose to 60 mL of deionized water and stir until completely dissolved to form a transparent solution with a concentration of 1.2 mol / L. The stirring speed is 600 r / min, and the stirring time is 1 h. Then transfer the transparent solution to a 100 mL polytetrafluoroethylene reaction kettle for hydrothermal reaction carbonization. The hydrothermal reaction temperature is 200 °C, the time is 24 h. After the reaction ends, naturally cool it to room temperature, take out the reaction product, wash it successively with absolute ethanol and deionized water and centrifuge it. After repeating the washing 6 times, carry out freeze-drying at a temperature of -70 °C, a vacuum degree of 10 Pa, and a drying time of 12 h to obtain black carbon microspheres;
[0049] Step 3: Place 5 g of the carbon microspheres obtained in Step 2 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and put it into a low-temperature tube furnace for high-temperature carbonization. The protective atmosphere used is argon, the temperature is 1000 °C, the holding time is 3 h, and the heating rate is 10 °C / min to obtain partially graphitized microcrystalline carbon spheres;
[0050] Step 4: Thoroughly grind and highly disperse and mix the molybdenum trioxide obtained in Step 1 and the microcrystalline carbon spheres obtained in Step 3 in a molar ratio of 1:0.5 to obtain a uniform mixed material;
[0051] Step 5: Place 10 g of the mixed material obtained in Step 4 in an alumina crucible with a length×width×height of 100 mm×40 mm×20 mm, and the thickness of the material layer is 8 mm. Put it into a low-temperature tube furnace for heat treatment. The protective atmosphere used is argon, the heat treatment temperature is 750 °C, the holding time is 2 h, and the heating rate is 30 °C / min to obtain near-spherical molybdenum dioxide powder;
[0052] Step 6: Place 20 g of the near-spherical molybdenum dioxide powder obtained in Step 5 in an alumina crucible with a length×width×height of 100 mm×40 mm×20 mm, and perform hydrogen reduction in a hydrogen-containing atmosphere. The hydrogen-containing atmosphere used is an inert gas with a hydrogen volume fraction of 90%. The reduction uses a gradient temperature rise reaction. The reaction temperatures are 650 °C, 750 °C, and 900 °C in sequence. The holding time for each stage is 2 h, and the heating rate is 20 °C / min to obtain near-spherical porous nano-molybdenum powder.
[0053] After testing, the particle size of the near-spherical porous nano-molybdenum powder prepared in this example is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%.
[0054] Example 3
[0055] This example includes the following steps:
[0056] Step 1: Place 150 g of ammonium molybdate in an alumina crucible with a length×width×height of 150 mm×150 mm×35 mm at room temperature, put it into a muffle furnace for decomposition reaction. The decomposition reaction temperature is 550 °C, the time is 2 h, and the heating rate is 40 °C / min. After the decomposition reaction ends, cool it to room temperature to obtain molybdenum trioxide;
[0057] Step 2: Add 5.4 g of glucose to 60 mL of deionized water and stir until completely dissolved to form a transparent solution with a concentration of 0.5 mol / L. The stirring speed is 500 r / min, and the stirring time is 0.5 h. Then transfer the transparent solution to a 100 mL polytetrafluoroethylene reaction kettle for hydrothermal reaction carbonization. The hydrothermal reaction temperature is 180 °C, the time is 12 h. After the reaction ends, naturally cool it to room temperature. Take out the reaction product and wash it successively with absolute ethanol and deionized water and centrifuge to separate. Repeat the washing 6 times and then perform freeze-drying. The temperature is -70 °C, the vacuum degree is 25 Pa, and the drying time is 10 h to obtain black carbon microspheres;
[0058] Step 3: Place 3 g of the carbon microspheres obtained in Step 2 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and put it into a low-temperature tube furnace for high-temperature carbonization. The protective atmosphere used is argon, the temperature is 600 °C, the holding time is 2 h, and the heating rate is 8 °C / min to obtain partially graphitized microcrystalline carbon spheres;
[0059] Step 4: Thoroughly grind and highly disperse and mix the molybdenum trioxide obtained in Step 1 and the microcrystalline carbon spheres obtained in Step 3 according to a molar ratio of 1:0.45 to obtain a homogeneous mixed material;
[0060] Step 5: Place 8 g of the mixed material obtained in Step 4 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and the thickness of the material layer is 3 mm. Put it into a low-temperature tube furnace for heat treatment. The protective atmosphere used is nitrogen, the heat treatment temperature is 700 °C, the holding time is 1 h, and the heating rate is 10 °C / min to obtain near-spherical molybdenum dioxide powder;
[0061] Step 6: Place 15 g of the near-spherical molybdenum dioxide powder obtained in Step 5 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and perform hydrogen reduction in a hydrogen-containing atmosphere. The hydrogen-containing atmosphere used is an inert gas with a hydrogen volume fraction of 90%. The reduction uses a gradient heating reaction, and the reaction temperatures are 650 °C, 700 °C, and 780 °C in sequence. The holding time for each stage is 1 h, and the heating rate is 10 °C / min to obtain near-spherical porous nano-molybdenum powder.
[0062] After testing, the particle size of the near-spherical porous nano-molybdenum powder prepared in this example is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%.
[0063] Figure 1 is the X-ray diffraction pattern of the molybdenum trioxide prepared in this example. From Figure 1 it can be seen that the structure of this sample is consistent with the MoO3 card with JCPDS number 05-0508, and there is no presence of other impurity phases, indicating that the product after the decomposition reaction of ammonium molybdate in this example is MoO3, and the purity of MoO3 is relatively high and the crystallinity is good.
[0064] Figure 2 is the scanning electron microscope image of the molybdenum trioxide prepared in this example. From Figure 2 it can be seen that this MoO3 is a block structure, the size is about 1 μm - 2 μm, and there are some larger particles.
[0065] Figure 3 is the X-ray diffraction pattern of the microcrystalline carbon spheres prepared in this example. From Figure 3It can be seen that the structure of this sample is consistent with the C material card with the JCPDS number 41-1487, indicating that the microcrystalline carbon spheres with the essence of C material are prepared by hydrothermal reaction carbonization and high-temperature carbonization in this invention.
[0066] Figure 4a And Figure 4b are the low-magnification and high-magnification scanning electron microscope images of the microcrystalline carbon spheres prepared in this example respectively. It can be seen from Figure 4a and Figure 4b that the microcrystalline carbon spheres are spherical structures with uniform sizes, and the size is about 1 μm.
[0067] Figure 5 is the X-ray diffraction pattern of the near-spherical molybdenum dioxide powder prepared in this example. It can be seen from Figure 5 that the structure of this sample is basically consistent with the MoO2 material card with the JCPDS number 32-0671, and there are characteristic peaks of a small amount of Mo4O 11 . This indicates that the reduction during heat treatment is incomplete, and there is a part of molybdenum trioxide that is not completely converted into Mo4O 11 . However, it does not affect the hydrogen reduction process of the next step. Therefore, the existence of a small amount of Mo4O 11 will not affect the reduction process and structure of Mo.
[0068] Figure 6a and Figure 6b are the low-magnification and high-magnification scanning electron microscope images of the near-spherical molybdenum dioxide powder prepared in this example respectively. It can be seen from Figure 6a and Figure 6b that the MoO2 is a near-spherical massive structure, and the size is about 500 nm - 900 nm.
[0069] Figure 7 is the X-ray diffraction pattern of the near-spherical porous nano-molybdenum powder prepared in this example. It can be seen from Figure 7 that the structure of this sample is basically consistent with the Mo material standard card with the JCPDS number 42-1120, and there are no other impurity phases. This indicates that the product prepared in this invention is molybdenum powder, and it has a high purity and good crystallinity.
[0070] Figure 8a and Figure 8b are the low-magnification and high-magnification scanning electron microscope images of the near-spherical porous nano-molybdenum powder prepared in this example respectively. It can be seen from Figure 8a and Figure 8b that the Mo powder is a near-spherical structure, the size is about 500 nm - 900 nm, and there are a large number of pore structures on the surface.
[0071] Example 4
[0072] This example includes the following steps:
[0073] Step 1: Place 160 g of ammonium molybdate in an alumina crucible with dimensions of length × width × height = 150 mm × 150 mm × 35 mm at room temperature, and put it into a muffle furnace for decomposition reaction. The temperature of the decomposition reaction is 580 °C, the time is 1.5 h, and the heating rate is 45 °C / min. After the decomposition reaction is completed, cool it to room temperature to obtain molybdenum trioxide;
[0074] Step 2: Add 10.8 g of glucose to 60 mL of deionized water and stir until completely dissolved to form a transparent solution with a concentration of 1 mol / L. The stirring speed is 550 r / min, and the stirring time is 1 h. Then transfer the transparent solution to a 100 mL polytetrafluoroethylene autoclave for hydrothermal reaction carbonization. The temperature of the hydrothermal reaction is 160 °C, the time is 18 h. After the reaction is completed, naturally cool it to room temperature, take out the reaction product, wash it successively with absolute ethanol and deionized water and centrifuge to separate. Repeat the washing 5 times and then perform freeze-drying at a temperature of -45 °C, a vacuum degree of 30 Pa, and a drying time of 9 h to obtain black carbon microspheres;
[0075] Step 3: Place 5 g of the carbon microspheres obtained in Step 2 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and put it into a low-temperature tube furnace for high-temperature carbonization. The protective atmosphere used is argon, the temperature is 600 °C, the holding time is 2.5 h, and the heating rate is 10 °C / min to obtain partially graphitized microcrystalline carbon spheres;
[0076] Step 4: Thoroughly grind and highly disperse and mix the molybdenum trioxide obtained in Step 1 and the microcrystalline carbon spheres obtained in Step 3 according to a molar ratio of 1:0.48 to obtain a uniform mixed material;
[0077] Step 5: Place 10 g of the mixed material obtained in Step 4 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and the thickness of the material layer is 3.5 mm. Put it into a low-temperature tube furnace for heat treatment. The protective atmosphere used is argon, the heat treatment temperature is 720 °C, the holding time is 1.5 h, and the heating rate is 15 °C / min to obtain nearly spherical molybdenum dioxide powder;
[0078] Step 6: Place 15 g of the nearly spherical molybdenum dioxide powder obtained in Step 5 in an alumina crucible with dimensions of length × width × height = 100 mm × 40 mm × 20 mm, and perform hydrogen reduction in a hydrogen-containing atmosphere. The hydrogen-containing atmosphere used is an inert gas with a hydrogen volume fraction of 90%. The reduction uses a gradient heating reaction, and the reaction temperatures are 620 °C, 720 °C, and 800 °C in sequence. The holding time for each stage is 0.5 h, and the heating rate is 15 °C / min to obtain nearly spherical porous nano-molybdenum powder.
[0079] After detection, the particle size of the near-spherical porous nano-molybdenum powder prepared in this embodiment is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%.
[0080] As mentioned above, the above are only the preferred embodiments of the present invention and do not impose any limitations on the present invention. Any simple modifications, changes, and equivalent changes made to the above embodiments according to the technical essence of the invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A preparation method of near-spherical porous nano-molybdenum powder, characterized in that, The method includes the following steps: Step 1: Decompose molybdate under room temperature conditions to obtain molybdenum trioxide. Step 2: Conduct hydrothermal reaction carbonization using an organic carbon source, and wash and dry the reaction product to obtain carbon microspheres. Step 3: Place the carbon microspheres obtained in Step 2 in a tube furnace for high-temperature carbonization to obtain partially graphitized microcrystalline carbon spheres. Step 4: Highly disperse and mix the molybdenum trioxide obtained in Step 1 with the microcrystalline carbon spheres obtained in Step 3 to obtain a homogeneous mixed material. Step 5: Place the mixed material obtained in Step 4 in a tube furnace for heat treatment to obtain near-spherical molybdenum dioxide powder. Step 6: Conduct hydrogen reduction on the near-spherical molybdenum dioxide powder obtained in Step 5 in a hydrogen-containing atmosphere to obtain near-spherical porous nano-molybdenum powder.
2. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 1, the molybdate is ammonium molybdate, the temperature of the decomposition reaction is 500°C to 700°C, the time is more than 1 h, and the heating rate is greater than 30°C / min.
3. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 2, the organic carbon source is the water-soluble organic carbon source glucose, and the organic carbon source is prepared into a solution with a concentration of 0.3 mol / L to 1.2 mol / L; the temperature of the hydrothermal reaction is 150°C to 200°C, and the time is 12 h to 24 h.
4. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 2, the drying treatment method is freeze-drying, the temperature does not exceed -40°C, the vacuum degree does not exceed 40 Pa, and the drying time is more than 8 h.
5. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 3, the protective atmosphere for the high-temperature carbonization is argon, the temperature is 500°C to 1000°C, the holding time is 1 h to 3 h, and the heating rate is 5°C / min to 10°C / min.
6. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 4, the molar ratio of the molybdenum trioxide to the microcrystalline carbon spheres is 1:0.4 to 0.
5.
7. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 5, the mixed material is placed in an alumina crucible, and the thickness of the material layer does not exceed 8 mm; the protective atmosphere for the heat treatment is argon or nitrogen, the heat treatment temperature is 600°C to 750°C, the holding time is 0.5 h to 2 h, and the heating rate does not exceed 30°C / min.
8. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 6, the hydrogen-containing atmosphere for the hydrogen reduction is an inert gas with a hydrogen volume fraction greater than 10%, the reduction uses a gradient heating reaction, the reaction temperature is 600°C to 900°C, and the holding time for each stage is 0.5 h to 2 h, and the heating rate is 5°C / min to 20°C / min.
9. The preparation method of a near-spherical porous nano-molybdenum powder according to claim 1, characterized in that, In Step 6, the particle size of the near-spherical porous nano-molybdenum powder is greater than 500 nm, the sphericity is greater than 0.6, and the porosity is greater than 20%.
Citation Information
Cited By
Molybdenum dioxide material, molybdenum powder and methods of making
CN122608085A